Маугли: [сказка] / [худ. И. Н. Приходкин] - Приходкин И. Н. (Фламинго, 2011)
Экземпляры: с/ф № 16 (20140424) / Инвентарный номер: 43335 / Цена: / Сис.шифр: 84И / Авт.знак: М 35 / ГРНТИ: 17.82.93 / ББК: 84(4)